Respuesta :

Answer:

F(y^2) = 1/ (y^2-3)

Step-by-step explanation:

F(x) = 1/ (x-3)

Replace x with y^2

F(y^2) = 1/ (y^2-3)

Answer: f(y^2) = 1/((1/(x-3))^2-3)

Step-by-step explanation:

To start to understand this equation realize y = f(x) but f(x) gives a little bit more information specifically to define x as whatever is in the parenthesis of f(_).

For example f(x) = x/2

so lets say x = 2

so "f(2) = 2/2" or "y = 1 when x = 2"

In this equation y or f(x) = 1/(x-3)

so to get f(y^2) = 1/(x-3)

square the value of y and plug it into 1/(x-3) as the value of x

f(y^2) = 1/(y^2-3)

ACCESS MORE